Strategi Pengasuhan Orang Tua Tunggal dalam Mengelola Emosi Remaja: Studi Kasus di Desa Ramba, Sosa Julu, Padang Lawas - Maslina Daulay; Ummi Syopiah Daulay; Hamdan Siregar (Jurnal Penelitian Pendidikan IPA, 2025)
This research is motivated by the high incidence of emotional disorders among adolescents in Ramba Village, Sosa Julu, Padang Lawas, who are raised by single parents with limited supervision and attention. This study aims to identify the types of emotional disorders experienced by adolescents, the parenting styles applied by single parents, and the supporting and inhibiting factors involved. This qualitative descriptive study was conducted in Ramba Village. Data were collected through purposive sampling from six single parents, ten adolescents aged 17 to 21 years, as well as neighbors, peers, and the village head. Data collection methods included non-participant observation, unstructured interviews, and documentation. Data validity was ensured through methodological triangulation. The results reveal from a psychobiological perspective that emotional disorders experienced by adolescents include anger, anxiety, and stress. Single parents apply both authoritarian and democratic parenting styles, with democratic parenting proven to be more effective in managing emotions. Supporting factors include family support and a positive social environment, while inhibiting factors include low parental education, limited time, and economic constraints. This study concludes that from a psychobiological approach, appropriate parenting styles, especially democratic parenting and environmental support, are very important for improving adolescents' emotional well-being.